Old Aged Quality of Life : Brazil – India a Cross-cultural Perspective - Figueira, Helena A., Figueira, Joana A., Bezerra, Jani C. and Dantas, Estélio H.M (Indian Journal of Gerontology, 2009)
With the purpose of serving as a reference on dealing with the old aged this cross-cultural research aimed to compare Quality of Life of aged from two opposite civilizations to establish parameters of impact on Quality of Life of old aged world-wide. Two non- selected low income samples of aged volunteers, one from Brazil (Figueira, 2008) and another one from India (Verma, 2008) were taken. In this correlational descriptive research, the old aged answered a WHOQOL questionnaire on Quality of Life, from World Health Organization (WHOQOL-Old and WHOQOL-100 respectively). Comparing their answers it was presented a comparison of priority, Quality of Life, in the themes of the questionnaires by the old aged of both populations. The statistical treatment contemplated two dimensional techniques of descriptive statistical: mean and standard deviation. The evaluation showed relation between life expectations and QOL. Death and dying revealed through the lowest QOL the existence of a substantial preoccupation in Brazil opposed to India. The same happened with present past and future activities. Satisfaction with past present and future raised the QOL level in India old aged opposed to that in Brazil. In general the Indian aged QOL finding was higher than that of Brazil’s low income old aged. This research confirms the inference of social adjustment influencing hopes and expectations in QOL. It also informs that Brazil’s old aged quality of life concerning death and dying plus future and present activities are lower than India’s. As both samples are composed by low income old aged the observed QOL was also low. It is suggested that works directed to the aged take in consideration this comparison of evaluation of quality of life by aged of two distinct civilizations